The novel form of amyloidosis derived from EGF‐containing fibulin‐like extracellular matrix protein 1 (EFEMP1) preferentially affects the lower gastrointestinal tract of elderly femalesa. Issue 3 (28th November 2020) - Dao, Linda N; Kurtin, Paul J; Smyrk, Thomas C; Theis, Jason D; Dasari, Surendra; Vrana, Julie A; Dispenzieri, Angela; Nasr, Samih H; McPhail, Ellen D
Abstract : Aims: To characterise the clinicopathological features of amyloidosis due to EGF‐containing fibulin‐like extracellular matrix protein 1 (EFEMP1), a newly described amyloid type. Methods and results: We identified cases by searching the Mayo Clinic amyloid liquid chromatography and tandem mass spectrometry typing database for specimens with the universal amyloid signature proteins, abundant EFEMP1 spectra and absence of other specific amyloid precursor proteins. We also developed an immunohistochemical stain for EFEMP1 applicable to formalin‐fixed tissue sections and performed electron microscopy in one case. We identified 33 specimens from 32 patients with EFEMP1 amyloid. Most patients were female (91%) with a mean age of 75 years, and most specimens (94%) were from the bowel. EFEMP1 amyloid was incidentally identified in specimens biopsied/resected for a variety of clinical indications. In bowel specimens, EFEMP1 amyloid involved blood vessels and interstitium of the lamina propria, submucosa and/or muscularis propria. Although the EFEMP1 deposits were weakly to moderately Congo red‐positive with absent to weak birefringence, they were strongly positive for EFEMP1 by immunohistochemistry, had the characteristic fibrillar ultrastructure of amyloid and were readily identified by mass spectrometry. Conclusions: EFEMP1 amyloid is a recently described novel amyloid type that predominantly affects the bowel of elderly females. Because EFEMP1 amyloid is only weakly Congo red‐positive, it may be overlooked without a high index of suspicion. However, its characteristic microanatomical distribution is highlighted by immunohistochemistry and its identity is readily confirmed by mass spectrometry. Based on its distinctive features, we propose that EFEMP1 amyloidosis be considered a new amyloid type.